2016
DOI: 10.1111/jfpp.13161
|View full text |Cite
|
Sign up to set email alerts
|

The effects of modified blanching and oregano essential oil on drying kinetics and sensory attributes of dried meat

Abstract: The effect of modified blanching treatments on the drying behavior of beef meat was evaluated by determining moisture ratio versus time curves and the influence on sensory quality of the resulting product. The three treatments under investigation were (1) oil treatment (OT) (2) steam blanching (SB), and (3) hot air blanching (HAB) with three doses of oregano essential oil (OEO) (1) 1.5 (2) 3, and (3) 6 mL. Each treatment had an effect on the drying time of the beef samples, however, the dose of OEO applied did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In this study, we focus on using TEO. The reason is twofold: First, there is a high demand from consumers to use natural products as alternative additives to improve food quality 16 ; Second, a previous study demonstrated positive results after using OEO during the meat drying process 22 . Hence, the method by the application of OEO during meat drying was extended to the use of other essential oils to control microbial load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we focus on using TEO. The reason is twofold: First, there is a high demand from consumers to use natural products as alternative additives to improve food quality 16 ; Second, a previous study demonstrated positive results after using OEO during the meat drying process 22 . Hence, the method by the application of OEO during meat drying was extended to the use of other essential oils to control microbial load.…”
Section: Discussionmentioning
confidence: 99%
“…Besides drying and marinade methods, there is a high demand from consumers to use natural products as an alternative to additives to improve food quality 16,17 . There has been a particular interest in the application of natural food additives for meat instead of classical synthetic preservatives 18,19,20,21 .…”
Section: Introductionmentioning
confidence: 99%